Organizational model of ensuring safety and quality of treatment of aggressive psychiatric patients in mental health nursing in Slovenia - Branko Gabrovec (Obzornik zdravstvene nege, 2014)
Introduction: The paper presents the organizational measures for managing violence in psychiatric settings and the study that introduces the preliminary success rate of the proposed model. Methods: For the purpose of this study a non-experimental sampling method was employed using a structured questionnaire as a data collection instrument. The sample covered the personnel most frequently exposed to violence namely, the nursing staff in closed and/or intensive psychiatric units in 5 Slovenian psychiatric hospitals, 3 psychiatric homes and 2 special education, and work and care centres. The data were statistically analysed with the SPSS v20 software package, with p < 0.05 indicating statistical significance. Results: The practical part of the functional training was conducted between 2010 and 2013 in specific psychiatric hospitals and wards. In a study carried out in 2013, preliminary results indicating the success rate of the proposed model were obtained. Discussion and conclusions: Health care workers in psychiatry are responsible for providing safe and high quality treatment even in cases of aggressive outbursts, but they lack the necessary functional knowledge to cope with aggression in the workplace. The paper presents an organizational model for ensuring the safety of the patients and the quality of their treatment in case of an aggressive outburst, along with the presentation of the required functional training.